Upaya Peningkatan Penjualan Melalui Pengurusan Perizinan Secara Online Single Submission (OSS) Mitra Usaha Produk Makanan di UMKM Medan Tuntungan - Kartika Sari Lubis; Edi Winata; Ade Rahma Ayu (JPM: Jurnal Pengabdian Masyarakat, 2021)
For business people, apart from capital and inventory, the thing that needs to be taken care of is an official permit from the government, for the smooth running of their business. Many business people overlook this one thing. Because most of them think that licensing is only needed by businesses that are already operating on a large scale. In addition, there are still many who think that getting a business license is complicated and takes a lot of time. This service activity aims to assist business partners in Medan Tuntungan in managing the IUMK as proof of the legality of the business activity concerned as an effort to increase sales results. , namely the Regulation of the Minister of Cooperatives and Small and Medium Enterprises Number 2 of 2019 concerning Electronically Integrated Business Licensing for Micro-Small Enterprises (“PermenkopUKM 2/2019”). This rule is a derivative of Government Regulation Number 24 of 2018 concerning Electronically Integrated Business Licensing Services (“PP on OSS”). The issuance of these two latest regulations further simplifies the procedure for applying for Micro and Small Business Permits (IUMK) for Micro and Small business actors. The target achieved in this service is to increase the income of the food product business that is incorporated in business partners in Medan Tuntungan MSMEs and be able to understand well the procedures for obtaining permits so that partners can develop market share and can compete with other competitors.